2013
DOI: 10.7897/2230-8407.04851
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Reaction Time in Basketball Players and Healthy Controls

Abstract: Reaction is purposeful voluntary response to different stimuli as visual or auditory stimuli. Auditory reaction time is time required to response to auditory stimuli. Quickness of response is very important in games like basketball. This study was conducted to compare auditory reaction time of basketball players and healthy controls. The auditory reaction time was measured by the reaction time instrument in healthy controls and basketball players. Simple reaction time and choice reaction time measured. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 10 publications
1
21
0
3
Order By: Relevance
“…[8][9][10][11][12][13] Developments resulting in reduced reaction times can be also observed in other sports disciplines. Hascelik et al [14] found decreases in the visual reaction time of male volleyball players, from 214.55 ms to 200 ms. Ghuntla et al [9] found significant shorter visual reaction time among basketball players when compared with that in the control group. Mamoglu et al [15] found that the visual reaction time among professional soccer players was shorter when compared with that among parttime soccer players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12][13] Developments resulting in reduced reaction times can be also observed in other sports disciplines. Hascelik et al [14] found decreases in the visual reaction time of male volleyball players, from 214.55 ms to 200 ms. Ghuntla et al [9] found significant shorter visual reaction time among basketball players when compared with that in the control group. Mamoglu et al [15] found that the visual reaction time among professional soccer players was shorter when compared with that among parttime soccer players.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Many researches show that more experienced players react more quickly than their less experienced counterparts, and there is significantly decreased reaction time in athletes as compared to nonathletic persons. [7,8] A study by Ghuntla et al [9] found that basketball players had faster reaction time than healthy controls. Another study carried out by Bhabhor et al [1] found decreases in the visual reaction time of table tennis players.…”
Section: Introductionmentioning
confidence: 99%
“…Response times have been shown to differentiate skill levels in sports such as basketball (Ghuntla et al 2012), sprinting (Tønnessen et al 2013), table tennis (Hughes et al 1993), handball (Zwierko 2007), water-polo (Kioumourtzoglou et al 1998), and rugby (Gabbett and Abernethy 2013), and therefore, the implementation of SVT into training routines may be key for the development of athletes. SVT is a relatively simple tool that maintains real-world context, can be conducted indoors, and, as seen with the present study, can be done with injured athletes.…”
Section: G2mentioning
confidence: 99%
“…it was found that sports training subjects having the shortest left hand mixed reaction time according to these averages, were statistically significantly lower (p <0.01) than those receiving arts education. Ghuntla et al (2012) compared basketball players to healthy adult control group and found that the former group had significantly shorter RZ data.…”
Section: Discussionmentioning
confidence: 99%